Zinc Oxide Nanoparticles Prime a Protective Immune Response in Galleria mellonella to Defend Against Candida albicans - Xu, Mei-nian; Li, Li; Pan, Wen; Zheng, Huan-xin; Wang, Meng-lei; Peng, Xiao-ming; Dai, Si-qi; Tang, Ying-mei; Zeng, Kang; Huang, Xiao-wen (Frontiers in Microbiology, 2021)
Purpose: Zinc oxide nanoparticles (ZnO-NPs) have exerted antimicrobial properties. However, there is insufficient evaluation regarding the in vivo antifungal activity of ZnO-NPs. This study aimed to investigate the efficacy and mechanism of ZnO-NPs in controlling Candida albicans in the invertebrate Galleria mellonella. Methods: G. mellonella larvae were injected with different doses of ZnO-NPs to determine their in vivo toxicity. Non-toxic doses of ZnO-NPs were chosen for prophylactic injection in G. mellonella followed by C. albicans infection. Then the direct in vitro antifungal effect of ZnO-NPs against C. albicans was evaluated. In addition, the mode of action of ZnO-NPs was assessed in larvae through different assays: quantification of hemocyte density, morphology observation of hemocytes, characterization of hemocyte aggregation and phagocytosis, and measurement of hemolymph phenoloxidase (PO) activity. Results: ZnO-NPs were non-toxic to the larvae at relatively low concentrations (≤ 20 mg/kg). ZnO-NPs pretreatment significantly prolonged the survival of C. albicans-infected larvae and decreased the fungal dissemination and burden in the C. albicans-infected larvae. This observation was more related to the activation of host defense rather than their fungicidal capacities. Specifically, ZnO-NPs treatment increased hemocyte density, promoted hemocyte aggregation, enhanced hemocyte phagocytosis, and activated PO activity in larvae. Conclusion: Prophylactic treatment with lower concentrations of ZnO-NPs protects G. mellonella from C. albicans infection. The innate immune response primed by ZnO-NPs may be part of the reason for the protective effects. This study provides new evidence of the capacity of ZnO-NPs in enhancing host immunity and predicts that ZnO-NPs will be attractive for further anti-infection applications.